2015
DOI: 10.1017/s0022215115002108
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular expression profile and clinical significance of the CCR9–CCL25 chemokine receptor complex in nasopharyngeal carcinoma

Abstract: The extent of CCR9 and CCL25 upregulation in nasopharyngeal carcinoma correlates with the tumour-node-metastasis stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In conclusion, disruption of the CCR9/ CCL25 axis in tumor bearers may affect homeostasis of the common lymphoid system and compromise the delicate balance between gut and systemic immunity (45). Nonetheless, several observations point to a cellautonomous role of CCR9/CCL25 in cancer cell migration, invasion, and metastatic dissemination as well as in PI3Kdependent resistance to chemotherapy (46)(47)(48)(49)(50)(51). Enforced CCR9 expression on colorectal cancer cells dictated their niching in mouse intestines after xenografting, whereas CCL25 blockade enhanced liver metastases (52).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, disruption of the CCR9/ CCL25 axis in tumor bearers may affect homeostasis of the common lymphoid system and compromise the delicate balance between gut and systemic immunity (45). Nonetheless, several observations point to a cellautonomous role of CCR9/CCL25 in cancer cell migration, invasion, and metastatic dissemination as well as in PI3Kdependent resistance to chemotherapy (46)(47)(48)(49)(50)(51). Enforced CCR9 expression on colorectal cancer cells dictated their niching in mouse intestines after xenografting, whereas CCL25 blockade enhanced liver metastases (52).…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies have indicated that CCR9 could be viewed as an oncogenic biomarker in predicting metastasis and prognosis for cancer patients. Increased expression of CCR9 and CCL25 have been identified in various tumors, such as nasopharyngeal carcinoma and ovarian cancer [9,31]. Upregulated expression of CCR9 and CCL25 were correlated with advanced tumor stage and poor overall survival [9,31].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, CCL25 and its specific receptor CCR9 play an important role in the proliferation and chemotaxis of inflammatory cells (Qiuping et al, 2004). Currently, research regarding CCR9/CCL25 is mostly concentrated in the fields of rheumatoid arthritis (Yokoyama et al, 2014), inflammatory bowel disease (Igaki et al, 2018), hepatitis (Nakamoto et al, 2012) and tumors (Ye, Huang, Zhang, & Chen, 2015). To better understand the role of CCR9/CCL25 in cancer, we highlight recent advances and provide a thorough evaluation of the CCR9/CCL25 mechanism of action in different types of cancer.…”
Section: Structure and Function Of Ccr9 And Ccl25mentioning
confidence: 99%
“…In addition, CCL25 facilitated the proliferation of nasopharyngeal carcinoma CNE‐2 cells in a concentration‐dependent manner. Knocking down CCR9 suppressed the CCL25‐induced proliferation of CNE‐2 cells, also in a concentration‐dependent manner (Ye et al, 2015). Clearly, CCR9/CCL25 is a powerful antiproliferative agent of cancer cells.…”
Section: Cellular Functions Of Ccr9/ccl25 In Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation